ENVIRONMENTAL SECURITY STRUCTURE FORMING THE GROUNDWORK FOR A TERRITORIAL ENVIRONMENTAL PASSPORT - A. L. Bolsherotov (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim. The aim of the study is to develop an environmental passport based on the structure of integrated environmental safety for construction projects. With each year that passes, environmental problems are coming increasingly to the fore. As part of mitigation efforts, an environmental passport is required to assess and control the environmental safety of construction areas and building sites.Method. The study is based on the development of a sound model of integrated environmental safety in construction projects and a methodology for calculating its indicators, in particular, the indicator of “degree of concentration”. The methodology of ranking the factors by importance is applied.Results. The structure of a building site's environmental passport is presented, taking the entire spectrum of its direct impact and environmental pollution into account, as well as the indirect impact, energy efficiency and autonomy of the site. The scope of the environmental passport comprises the entire building lifecycle, from design to operation and liquidation. An environmental passport en-ables the identification of problematic impacts on the geophraphical area from an environmental point of view, as well as giving recommendations for resolving problems. The threshold of environ-mental safety is set for each geographical area under assessment (i.e., for each building project and geographical area, it is determined by the composition of relevant factors) and the existing level of environmental pollution is determined along with the ecological reserve of the area and its steady state range, i.e., the acceptable level of deviation of environmental safety indicators, which depends on temporary factors and the objective reality of the functioning of the infrastructure of the evaluated territory. For the design and construction of building projects, indicators of environmental reserve and technogenic pressure of the facility are of fundamental importance when making decisions.Conclusion. The article presents a rational assessment of the main indicators of the environmental pass-port, providing the structure of a comprehensive assessment of environmental safety. The research results are presented and the scope of the environmental passport proposed in the assessment of geo-graphical areas and evaluation of facilities and design.